Impact of Structured Diabetes Pharmaceutical Care Training on Practices of Community Pharmacist - Pawar, Sunita; Pawar, Atmaram (Journal of Pharmacy Practice and Community Medicine)
Objectives: The diabetes epidemic in India has placed it in the second position in having the largest number (77 million) of adults with diabetes, worldwide. Diabetes is a chronic progressive disease that can be effectively controlled by medication adherence, monitoring and managing well on regular basis. A well-trained pharmacist can help the patients to achieve good glycaemic control by providing them pharmaceutical care. This study aims to evaluate the effect of tailored diabetes pharmaceutical-care training on the practices of pharmacists and the subsequent impact on patients’ clinical outcomes. Methods: A prospective interventional quantitative study was conducted to assess the impact on Knowledge, Attitude and Practice (KAP) levels of community pharmacists after providing diabetes pharmaceutical care training. The selected trained pharmacists enrolled type-2 diabetes patients to assess the practice component further, by observing patients’ outcomes in terms of knowledge, attitude, practices along with clinical outcomes in terms of glycemic control, post pharmaceutical care provision. A descriptive analysis and statistical evaluation, using SPSS Version 21. Key Findings: Significantly improved outcomes were observed across all the pharmacist participants in terms of KAP levels, from baseline to post-interventional training (p<0.0001). Also, a considerable impact on patients' knowledge, awareness, practices and clinical outcomes was noted in the intervention group. Clinically there was a significant reduction in fasting blood glucose levels, postprandial blood glucose levels, HbA1c and control in systolic and diastolic blood pressure (p<0.05) was also observed. Conclusion: Community pharmacists who had completed structured training in diabetes care could practice pharmaceutical- care well and help patients with type-2 diabetes in achieving good glycemic control.
Keywords: Diabetes; Pharmaceutical care; Community pharmacist; Training; Impact